Literature Study: Analysis of Polygamy Factors in Men - Mufarochah Mufarochah; Nafan Tarihoran; Asfandi Asfandi (Green Publisher Indonesia, 2025)
This research aims to determine the underlying factors in men who are polygamous. This research uses a literature study method to look for aspects that underlie men's desire to carry out polygamy, using a data accumulation scheme via Mendeley and Google Scholar to access journals and scientific works. A literature search was carried out using the keywords